ChemInform Abstract: Chrotacumines G—J, Chromone Alkaloids from Dysoxylum acutangulum with Osteoclast Differentiation Inhibitory Activity. Issue 39 (23rd September 2014) - Morita, Hiroshi; Nugroho, Alfarius Eko; Nagakura, Yuta; Hirasawa, Yusuke; Yoshida, Haruka; Kaneda, Toshio; Shirota, Osamu; Ismail, Intan Safinar
Abstract The chromone alkaloids, chrotacumines G‐J [(Ia)‐(Id)] are obtained from the barks of Dysoxylum acutangulum.